ARV-825 Demonstrates Antitumor Activity in Gastric Cancer via MYC-Targets and G2M-Checkpoint Signaling Pathways - Liao, Xinmei; Qian, Xiaoqing; Zhang, Zimu; Tao, Yanfang; Li, Zhiheng; Zhang, Qian; Liang, Hui; Li, Xiaolu; Xie, Yi; Zhuo, Ran; Chen, Yanling; Jiang, You; et al. (Frontiers in Oncology, 2021)
Objective Suppression of bromodomain and extra terminal (BET) proteins has a bright prospect to treat MYC-driven tumors. Bromodomain containing 4 (BRD4) is one of the BET proteins. ARV-825, consisting of a BRD4 inhibitor conjugated with a cereblon ligand using proteolysis-targeting chimera (PROTAC) technology, was proven to decrease the tumor growth effectively and continuously. Nevertheless, the efficacy and mechanisms of ARV-825 in gastric cancer are still poorly understood. Methods Cell counting kit 8 assay, lentivirus infection, Western blotting analysis, Annexin V/propidium iodide (PI) staining, RNA sequencing, a xenograft model, and immunohistochemistry were used to assess the efficacy of ARV-825 in cell level and animal model. Results The messenger RNA (mRNA) expression of BRD4 in gastric cancer raised significantly than those in normal tissues, which suggested poor outcome of patients with gastric cancer. ARV-825 displayed higher anticancer efficiency in gastric cancer cells than OTX015 and JQ1. ARV-825 could inhibit cell growth, inducing cell cycle block and apoptosis in vitro. ARV-825 induced degradation of BRD4, BRD2, BRD3, c-MYC, and polo-like kinase 1 (PLK1) proteins in four gastric cancer cell lines. In addition, cleavage of caspase 3 and poly-ADP-ribose polymerase (PARP) was elevated. Knockdown or overexpression CRBN could increase or decrease, respectively, the ARV-825 IC50 of gastric cancer cells. ARV-825 reduced MYC and PLK1 expression in gastric cancer cells. ARV-825 treatment significantly reduced tumor growth without toxic side effects and downregulated the expression of BRD4 in vivo. Conclusions High mRNA expression of BRD4 in gastric cancer indicated poor prognosis. ARV-825, a BRD4 inhibitor, could effectively suppress the growth and elevate the apoptosis of gastric cancer cells via transcription downregulation of c-MYC and PLK1. These results implied that ARV-825 could be a good therapeutic strategy to treat gastric cancer.